Accounting System Implementation Study in CV. Yummys Motherlacto Indonesia Company to Increase Transparency and Accountability: Kajian Implementasi Sistem Akuntansi Pada Perusahaan CV. Yummys Motherlacto Indonesia Untuk Meningkatkan Transparansi Dan Akuntabilitas - Rizky Keyla Agatha; Hesty Prima Rini (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
CV. Yummys Motherlacto Indonesia is a company that produces and distributes nutritious products, maternal and infant care. In improving financial transparency and accountability, this company implements accounting software. This internship activity was carried out by assessing the effectiveness of software use. The assessment was carried out using the interview method with related parties. The results of the interview analysis showed that the software improved financial transparency and accountability by facilitating transaction recording, financial reporting, and access to information for stakeholders. The obstacles faced in the implementation were the lack of staff understanding of the software, suboptimal use of features, and limited human resources in the IT field. The proposed solution is to conduct ongoing training for staff and improve human resources for IT experts. Thus, it can be concluded that the implementation of this software is effective in improving the company's financial governance, although improvements are needed in several aspects.